Role of Salivary Glucose in the Diagnosis and Monitoring of Type 2 Diabetes Mellitus - Humaira Abid, Muhammad Nadim Akbar Khan, Shazia Qayyum, Fakhra Noureen, Rubina Shafi, Amina Kanwal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the correlation of fasting salivary glucose with fasting plasma glucose (FPG) and glycated hemoglobin A1c (HbA1c) for the diagnosis and monitoring of type 2 diabetes mellitus (T2DM). Methods: A case - control study was carried out from 11th March to 30th August 2021, involving 88 participants out of which 44 were healthy controls and 44 participants were known T2DM who had FPG ≥ 126 mg/dl or 7.0 mmol/L. FPG was measured by Glucose oxidase method and HbA1c by National Glycohemoglobin Standardization Program (NGSP) certified chromatography. Results: T2DM group had significantly higher FPG, HbA1c and salivary glucose values. Both diabetics and healthy controls showed a positive correlation of fasting salivary glucose with FPG. The correlation coefficient (r) was 0.689 and 0.477 for cases and control groups respectively. Similarly, a positive correlation of fasting salivary glucose with HbA1c was observed with the value of r 0.433 and 0.498 for diabetic and healthy control groups respectively, when measured separately. For both groups linear regression equations were derived and scatter dot plots were plotted. P value < 0.001 Conclusion: A positive correlation of fasting salivary glucose with FPG and HbA1c was found. As a result, fasting salivary glucose can be utilized instead of plasma glucose for T2DM patients’ screening, diagnosis, and monitoring thereby eliminating the repeated pricks and mental trauma of patients. Keywords: Blood glucose, glycemia, glycated hemoglobin, salivary glucose, Type 2 diabetes mellitus